Model Persuasif Guru Dalam Mengkonseling Pelajar Guna Menggunakan Pakaian Syar’i Di Madrasah Aliyah Persiapan Negeri Besitang - Lilis Handayani; Kahar Muzakir (COMPASS: Journal of Education and Counselling, 2023)
This study describes the teacher's persuasion model in counseling students to use syar'i clothing at the Besitang state preparatory madrasah aliyah. The purpose of this research is to educate students and readers to always wear clothes that are based on Islamic religious guidelines. This type of research is a qualitative research that seeks to describe social phenomena that are currently developing in the masses today, the results of this research have been found, namely: First, the role of parents of students is needed to always provide advice to their children so that they always prioritize dress ethics. , Second, madrasa teachers always provide education to students so that they cover their private parts when they are in the madrasa environment and in the community environment by using humanist and persuasive language. Third, madrasa teachers will give sanctions to students if they violate dress procedures while in the madrasa environment.